IIUMeMall: a digital marketplace for campus - Hassan, Al Mamun; Ahmad Rasidi, Ahmad Hakimi; Zakaria, Noor Azura; Nasser Fadaaq, Wafaa Haussain; Tajuddin, Taniza; Suryady, Zeldi (IEEE, 2025)
IIUMeMall addresses the challenges faced by IIUM students residing in Mahallah, where limited access to essential items, especially food, is a common issue due to the absence of nearby cafes or stores. Current alternatives, such as visiting other Mahallahs or relying on runners, are inconvenient and lack transparency. IIUMeMall introduces a user-friendly website for seamless ordering and delivery of food and essentials within the IIUM campus. The platform enables students to explore menus, place orders, and make online or cash payments, with reliable couriers ensuring swift delivery to specified locations. The objectives include developing a user-friendly website that tailored to IIUM community, providing efficient order placement and secure payment options, and collaborating with couriers for timely delivery. The research project significantly enhances accessibility, convenience, and transparency, thereby improving the overall campus experience for IIUM students. The research project implements an agile methodology that facilitates regular feedback from students, support iterative development, and platform enhancement, resulting in a user-centric and accessible solution. A thorough testing process was followed, which included usability testing to make sure the system satisfies user needs and backend testing with Postman to verify the API operation. The targeted users benefit from easy access to a diverse range of food options and essentials, with the website providing a time-saving and reliable solution.